Associations between dietary patterns and parameters of ovarian reserve in Polish women of reproductive age - Dorota Szczęsna; Kinga Polańska; Paweł Radwan; Michał Radwan; Hassan Kassassir; Paulina Mroczek; Joanna Jurewicz (International Journal of Occupational Medicine and Environmental Health)
Objectives Research investigating the association between reproductive health and diet has predominantly focused on the antenatal and prenatal periods, as well as childbirth in women, and semen quality in men. There is a limited amount of research addressing female fertility assessed as ovarian reserve in relation to diet. The main aim of this study was to evaluate the association between dietary patterns and the parameters of ovarian reserve, such as antral follicle count (AFC), anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH), and estradiol (E2) – predictors of reproductive health in women of childbearing age.